CALCULATION OF RADON DIFFUSION COFFICIENT AND DIFFUSION LENGTH IN SOME SOILS TYPES - & eta l., Ali (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
In this study, the effect of humidity on the diffusion coefficient of radon gas and the diffusion length was studied  in different soils .We have used a modern device( SARAD German-made)was used to calculate the concentration of radon in different degrees of humidity and temperature. After linking it to the exposure system for radon, which was made by the researchers ,results obtained for soil indicated to a great agreement between the theoretical(predicted) and practical (measured) values ​​of the results of this study. ​​The study also indicated that diffusion coefficient decreased at slightly increasing of humidity by (10% -60%) of the diffusion coefficient results in the low humidity levels, which are less than 40% with a significant increase of more than(10%-60%)for humidity levels greater than 40% .Also for the diffusion length, it decreases with increasing of humidity.